Glycine transport accounts for the differential role of glycine vs. D-serine at NMDA receptor coagonist sites in the salamander retina - Stevens, Eric R. (2010)
In this study, we demonstrate that D-serine interacts with N-methyl-D-aspartate receptor (NMDAR) coagonist sites of retinal ganglion cells of the tiger salamander retina by showing that exogenous D-serine overcomes the competitive antagonism of 7-chlorokynurenic acid for this site. Additionally, we show that exogenous D-serine was more than 30 times as effective at potentiating NMDAR currents compared with glycine. We thus examined the importance of glycine transport through the application of selective antagonists of the GlyT1 (NFPS) and GlyT2 (ALX-5670) transport systems, while simultaneously evaluating the degree of occupancy of the NMDAR coagonist binding sites. Analysis was carried out with electrophysiological recordings from the inner retina, including whole-cell recordings from retinal ganglion cells and extracellular recordings of the proximal negative field potential. Blocking the GlyT2 transport system had no effect on the light-evoked NMDAR currents or on the sensitivity of these currents to exogenous D-serine. In contrast, when the GlyT1 system was blocked, the coagonist sites of NMDARs showed full occupancy. These findings clearly establish the importance of the GlyT1 transporter as an essential component for maintaining the coagonist sites of NMDARs in a non-saturated state. The normal, unsaturated state of the NMDAR coagonist binding sites allows modulation of the NMDAR currents, by release of either D-serine or glycine. These results are discussed in light of contemporary findings which favor D-serine over glycine as the major coagonist of the NMDARs found in ganglion cells of the tiger salamander retina.